Particulate matter air pollution and racial differences in cardiovascular disease risk - Erqou, Sebhat (Arterioscler Thromb Vasc Biol, 2018)
OBJECTIVE: We aimed to assess racial differences in air pollution exposures to ambient fine particulate (PM(2.5)) and black carbon (BC) and their association with cardiovascular disease (CVD) risk factors, arterial endothelial function, incident CVD events and all-cause mortality. APPROACH AND RESULTS: Data from the Heart Strategies Concentrating on Risk Evaluation (HeartSCORE) study were used to estimate one-year average air pollution exposure to PM(2.5) and BC using land-use regression models. Correlates of PM(2.5) and BC were assessed using linear regression models. Associations with outcomes were determined using Cox proportional hazards models, adjusting for traditional CVD risk factors. Data were available on 1,717 participants (66% female, 45% Blacks, 59±8 years). Blacks had significantly higher exposure to PM(2.5) (mean 16.1±0.75 vs. 15.7±0.73μg/m(3), p=0.001) and BC (1.19±0.11 vs. 1.16±0.13abs, p=0.001) compared to Whites. Exposure to PM(2.5), but not BC, was independently associated with higher blood glucose and worse arterial endothelial function. PM(2.5) was associated with a higher risk of incident CVD events and all-cause mortality combined over median follow-up of 8.3 years. Blacks had 1.45 (95% CI:1.00,2.09) higher risk of combined CVD events and all-cause mortality than Whites in models adjusted for relevant covariates. This association was modestly attenuated with adjustment for PM(2.5). CONCLUSION: PM(2.5) exposure was associated with elevated blood glucose, worse endothelial function, and incident CVD events and all-cause mortality. Blacks had a higher rate of incident CVD events and all-cause mortality than Whites that was only partly explained by higher exposure to PM(2.5.)